First Record of Palpita persimilis (Lepidoptera, Crambidae) and Oxycenus maxwelli (Acari, Eriophyidae) in South-eastern Uruguay - Burla Lemos, Juan Pablo; Castiglioni, Enrique; Navia, Denise; Aldabe, Joaquín (Agrociencia Uruguay, 2019)
Olive production has increased in recent years in Uruguay. In the south-eastern region, where oceanic influence leads to humid climatic conditions, some pests associated with foliar and fruit damage are not well known. Blacklight traps, a portable vacuum aspirator and observation of olive shoots were employed for a survey of adults and larvae of Lepidoptera and mites in an olive orchard from November 2016 to April 2017, in Rocha, Uruguay. Lepidopterous larvae increased from December to March, while adults reached a maximum in February. Larvae abundance was higher on cv Arbequina than on cv Coratina and cv Picual. Eriophyid mites were more abundant in December and their population decreased through the sampling period. This is the first report for Palpita persimilis (Lepidoptera, Crambidae) and Oxycenus maxwelli (Acari, Eriophyidae) in olive trees in Uruguay.